Study of the basic provisions of strategic marketingin - Bolyuch, I. O.; Pererva, P. G. (My University, 2023)
In the conditions of a market economy, the success of an industrial enterprise mostly depends on an effective development strategy, an extremely important place is occupied by its marketing strategy, which forms the market strategic orientations of the enterprise.
Keywords: production; strategic marketing; market; demand; price; supply